Smart Contracts for Secure and Transparent Payroll Management - Khair, Md Abul (Asian Accounting and Auditing Advancement, 2022)
To improve stakeholder confidence and expedite operations, this study explores the use of smart contracts for safe and transparent payroll management. The main goals are examining the advantages and difficulties of implementing innovative agreements, determining the factors most important for adoption, and investigating the policy ramifications for industry standards and regulatory frameworks. A thorough analysis of all available material, including papers from conferences, scholarly publications, and business reports, is part of the technique. Significant research reveals the potential advantages of smart contracts in terms of payroll process automation, efficiency, security, and transparency. However, there are drawbacks, including legislative uncertainty, technical complexity, scalability constraints, interoperability problems, and training requirements. To support the implementation of smart contracts for payroll management, policy implications emphasize the significance of precise legal frameworks, digital literacy programs, interoperability standards, and security best practices. This study advances knowledge about intelligent contracts' role in updating payroll administration procedures and provides insight to industry stakeholders, legislators, and businesses looking to use this cutting-edge technology.